Epidemiological Study of Pesticide Poisoning in Domestic Animals and Wildlife in Portugal: 2014–2020 - Grilo, Andreia; Moreira, Anabela; Carrapiço, Belmira; Belas, Adriana; São Braz, Berta (Frontiers in Veterinary Science, 2021)
Nowadays the intentional poisoning of domestic and wild animals is a crime in the European Union (EU), but as in the past the poison is still used in rural areas of a number of European countries to kill animals that were considered harmful for human activities. From January 2014 up until October 2020, the Laboratory of Pharmacology and Toxicology of the Faculty of Veterinary Medicine (LFT- FMV) has done analytical detection of poisoning substances in 503 samples of wildlife and domestic animals and pesticides residues were found in 239 of the samples analysed. In this retrospective study, toxicology results from domestic species (dog, cat, sheep, cows and horses), wildlife species (red foxes, birds of prey, lynx and wild boar) and food baits, are presented. During this period the samples analyzed at the LFT -FMV, were received from all over the country. Analytical detections were performed via solvent extraction followed by thin layer chromatography. Molluscicides (47%, n=109) and Carbamates (24%, n=57) were found to be the first category of pesticides involved in intoxications, in both domestic and wild animals, followed by rodenticides (13%, n=30) - in this group second and third generation, were the most represented; Strychnine is the third (11%, n=26) even though this pesticide has been banned in Portugal since 1988 and in the European Union since 2006 and finally Organophosphates (5%, n=11) in the small number. This study allowed to realize that a great number of positive samples involved banned pesticides (i.e. Aldicarb and Strychnine) but, at the same time, many positives cases were due to the exposure to commercially available products (i.e. Methiocarb and Anticoagulant rodenticides). Also, it’s possible to identify the areas where domestic species are the most affected (i.e. Setubal and Lisboa) and the areas where the wild animals are the mainly affected species (i.e. Faro, Castelo Branco and Bragança).